Misincorporations of amino acids in p53 in human cells at artificially constructed termination codons in the presence of the aminoglycoside Gentamicin - Pawlicka, Kamila; Henek, Tomas; Uhrik, Lukas; Hernychova, Lenka; Padariya, Monikaben; Faktor, Jakub; Makowiec, Sławomir; Vojtesek, Borivoj; Goodlett, David; Hupp, Ted; Kalathiya, Umesh (Frontiers in Genetics, 2024)
Readthrough of a translation termination codon is regulated by ribosomal A site recognition and insertion of near-cognate tRNAs. Small molecules exist that mediate incorporation of amino acids at the stop codon and production of full-length, often functional protein but defining the actual amino acid that is incorporated remains a challenging area. Herein, we report on the development a human cell model that can be used to determine whether rules can be developed using mass spectrometry that define the type of amino acid that is placed at a premature termination codon (PTC) during readthrough mediated by an aminoglycoside. The first PTC we analyzed contained the relatively common cancer-associated termination signal at codon 213 in the p53 gene. Despite of identifying a tryptic peptide with the incorporation of an R at codon 213 in the presence of the aminoglycoside, there were no other tryptic peptides detected across codon 213 that could be recovered; hence we constructed a more robust artificial PTC model. P53 expression plasmids were developed that incorporate a string of single synthetic TGA (opal) stop codons at S 127 P 128 A 129 within the relatively abundant tryptic p53 peptide 121-SVTCTYSPALNK-132. The treatment of cells stably expressing the p53-TGA 129 mutation, treated with Gentamicin, followed by immunoprecipitation and trypsinization of p53, resulted in the identification R, W, or C within the tryptic peptide at codon-TGA 129 ; as expected based on the two-base pairing of the respective anticodons in the tRNA to UGA, with R being the most abundant. The incorporation of amino acids at codons 127, 128, or 129 generally result in a p53 protein that is predicted to be 'unfolded' or inactive as defined by molecular dynamic simulations presumably because the production of mixed wild-type p53 and mutant oligomers are known to be inactive through dominant negative effects of the mutation. The data highlight the need to not only produce novel small molecules that can readthrough PTCs or C-terminal termination codons, but also the need to design methods to insert the required amino acid at the position that could result in a 'wild-type' functional protein.